Toxicokinetics and toxicity of potassium 2-(1-hydroxypentyl)-benzoate in beagle dogs. Issue 4 (3rd April 2017) - Li, Jiang; Wang, Xiao-Liang; Wang, Ai-Ping; Xu, Shao-Feng; Jin, Hong-Tao
Abstract: Potassium 2-(1-hydroxypentyl)-benzoate (dl-PHPB) is a prodrug of 3-n-butylphthalide (dl-NBP) for treatment of cerebral ischemic stroke in China, which undergoes lactonization to form dl-NBP in plasma. And, the phase II–III clinical trial of dl-PHPB has been approved by China Food and Drug Administration (CFDA) in 2013. In this study, a toxicity and toxicokinetics evaluation of dl-PHPB was performed using beagle dogs at specially high-dose 108 mg/kg/day (65-fold higher than humans at MHRD) for 4 weeks by intravenous administration, with a 3-week recovery period. And the plasma concentrations of dl-PHPB along with its metabolite dl-NBP were determined by HPLC-UV method. The results showed that dl-PHPB was quickly metabolized into dl-NBP, and no significant accumulation was observed. A slight to moderate behavior-associated toxicity was revealed in the process of delivery; and recovered to normal at the end of administration. Changes in the blood hematological profiles included significantly increased NEUT levels and lower LYM% content. Meanwhile, a notable increase in TG content was also observed in the serum biochemical parameters at 4-week post-exposure. These findings were reversible during the recovery period. The information from these studies would be taken into consideration for the interpretation of toxicology findings and provide a reference for clinical safety assessment. Abstract :